The Incidence and Risk Factors of Falls During Pregnancy - Paula Drabiščáková; Júlia Hederlingová; Petra Oťapková; Natália Dominová; Miroslava Jurčišinová; Zuzana Chválna; Jozef Záhumenský (IMR Press, 2022)
Background: During pregnancy, many hormonal, anatomical, and musculoskeletal changes occur. These changes alter the postural balance and increase the risk of falls. Falls during pregnancy can cause maternal and foetal injuries. In our analysis, we focused on women who fell as a result of gait and balance alterations. The primary objective of this study was to evaluate the incidence of falls in our study population. The secondary objective was to identify the risk factors for falls during pregnancy. Methods: 165 healthy singleton pregnant women were included in the study. The participants were asked to complete a questionnaire regarding their sociodemographic information, baseline health status and medical history, a detailed interview about potential falls during pregnancy, and a Modified Falls Efficacy Scale (MFES) questionnaire. A blood sample was taken to determine the baseline total circulating 25-hydroxyvitamin D (25(OH)D) level. Based on the evaluation of the questionnaires, we then divided the participants into two groups-the first group consisted of women who experienced a fall during pregnancy, and the rest of the participating pregnant women were included in the control group. Comparing the two groups, we analysed selected demographic data and a number of other variables including weight gain, the amount of exercise performed during pregnancy, and the participants' vitamin D levels. Results: The incidence of falls in our study was 12.73%. We found that age was the only statistically significant independent risk factor for falls during pregnancy (p-value: 0.0267). We found no statistical difference between the two groups regarding their levels of serum vitamin D. We also compared relevant variables in patients who feared the possibility of a fall and those who did not. We concluded that this fear was mainly associated with participants with BMI >25 (p-value: 0.0037 [RR: 2.31; 95% CI: 1.24-4.33]), while the feeling of improved postural stability was observed in women with regular exercise patterns (defined as physical exercise more than a 3 times per week) (p-value: 0.0377 [RR: 0.17; 95% CI: 0.03-1.22]). Conclusions: We did not manage to establish any isolated risk factors of falls during pregnancy except that of a higher age. In contrast to other studies, we did not confirm that regular exercise lowers the risk of falls, only that it improves self-confidence in the postural stability of pregnant women. Further study with objective quantification of postural and dynamic stability of pregnant women by using computerised static posturography may help to identify more accurately the risk group of pregnant patients. This will be the aim of our further work.